Medium Optimization for Recombinant Human Papillomavirus Type 52 L1 Protein Production in Pichia pastoris GS115 Platform on Bioreactor Scale - Apon Zaenal Mustopa; Febriyanti Nur Amani; Herman Irawan; Ela Novianti; Sri Swasthikawati; Nurlaili Ekawati; Maritsa Nurfatwa; Daniel Joko Wahyono; Ario Betha Juanssilfero; Jendri Mamangkey; Yudi Purnomo; Ai Hertati; et al. (Hayati Journal of Biosciences)
Human papillomavirus (HPV) stands as the primary etiological agent in the development of invasive cervical cancer worldwide. The L1 protein is a pivotal constituent of prophylactic HPV vaccines. Notably, HPV type 52 is one of the most prevalent genotypes found in squamous cell carcinoma cases in Indonesia. This research endeavor aims to enhance the productivity of recombinant HPV-52 L1 protein by optimizing the culture conditions of P. pastoris GS115 cells. In this study, we conducted trials employing 17 different media variants to optimize the expression of recombinant HPV-52 L1 protein. The results from small-scale experiments revealed three media, namely SYN6.10, BMMY, and SYN6.1, which exhibited promising yields of recombinant HPV-52 L1 protein as assessed through ELISA or immunoassay analysis. We succeeded in refining the SYN6.10 derivative, denoted as SYN6.10b, specifically designed for use in 1-L and 5-L bioreactors. This achievement was realized by adjusting Trace Element Solution (TES) and Vitamin Solution (VS) concentrations and implementing a methanol fed-batch phase with the addition of 0.3% methanol after 24 and 48 hours of fermentation in the P. pastoris medium. Further visualizations through SDS-PAGE and western blot analysis confirmed the protein after 72 hours of fermentation in a 1-L bioreactor using the SYN6.10b medium. In conclusion, the SYN6.10b medium required a 72 hours fermentation period to successfully express recombinant HPV-52 L1 protein in the P. pastoris platform.